Interpreting Concept Learning in Cognitive Informatics and Granular Computing - Yao, Yiyu (IEEE transactions on systems, man and cybernetics. Part B, Cybernetics, 2009)
Cognitive informatics and granular computing are two emerging fields of study concerning information and knowledge processing. A central notion to this processing is information and knowledge granularity. Concepts, as the basic units of thought underlying human intelligence and communication, may play a fundamental role when integrating the results from the two fields in terms of information and knowledge coding, representation, communication, and processing. While cognitive informatics focuses on information processing in the abstract, in machines, and in the brain, granular computing models such processing at multiple levels of granularity. In this paper, we examine a conceptual framework for concept learning from the viewpoints of cognitive informatics and granular computing. Within the framework, we interpret concept learning based on a layered model of knowledge discovery.